2012
DOI: 10.1002/hup.2216
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of kava and oxazepam on anxiety, mood, neurocognition; and genetic correlates: a randomized, placebo‐controlled, double‐blind study

Abstract: Acute "medicinal level" doses of this particular kava cultivar in naive users do not provide anxiolytic activity, although the phytomedicine also appears to have no negative effects on cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The previous study indicates that kavalactones were responsible for the inhibitory properties of kava, rather than other constituents such as the ubiquitous flavonoids (Sarris et al, 2012). But in the present study, we found that the major constituent of chalcones derived from kava extracts was also contributed to the inhibitory properties of kava.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The previous study indicates that kavalactones were responsible for the inhibitory properties of kava, rather than other constituents such as the ubiquitous flavonoids (Sarris et al, 2012). But in the present study, we found that the major constituent of chalcones derived from kava extracts was also contributed to the inhibitory properties of kava.…”
Section: Discussionmentioning
confidence: 48%
“…But in the present study, we found that the major constituent of chalcones derived from kava extracts was also contributed to the inhibitory properties of kava. Compared with the other extracts of kava plant, study by Zi et.al showed that feeding of UPII-SV40T transgenic mice with FKA for 290 days did not result in any noticeable toxicity (Sarris et al, 2012). Therefore, FKA might be a more valuable natural antitumor compound to be developed.…”
Section: Discussionmentioning
confidence: 97%
“…Another extract demonstrated effects similar to those of buspirone and opipramol, prescription drugs used for anxiety and depression (Boerner et al, ). Aqueous extracts of kava have also been investigated by Sarris et al () who reported their anxiolytic activity to be better than placebo with short‐term (3 weeks) use but not as effective as oxazepam when given in acute doses for 1 week (Sarris et al, ). In another study, this extract increased sexual drive in female users and reduced anxiety significantly (Sarris, Stough, Teschke, et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the State‐Trait Anxiety Inventory‐State, oxazepam caused an acute reduction in anxiety ( P = .035) while kava extract provided no impact ( P = .87) and placebo tended to increase anxiety ( P = .08). Using the Bond‐Lader “calm” scale, oxazepam provided significant calming ( P = .002), while kava extract ( P = .88) and placebo ( P = .20) did not . The lack of acute anxiety suppression is not a surprising finding, however.…”
Section: Kava Use In Anxietymentioning
confidence: 92%
“…In 2012, the first direct comparison of kava extract and a benzodiazepine was published . Participants (n = 22) with mild to moderate anxiety (HAM‐A total scores of 14‐25) but without bipolar, major depressive, or psychotic disorders were enrolled.…”
Section: Kava Use In Anxietymentioning
confidence: 99%